ChemInform Abstract: A New Concept for Electroless Nickel Plating: Aluminum as Reducing Agent. Issue 26 (June 2016) - Zhang, Xingkai; Zhang, Junyan
Abstract: Nickel coatings on Cu substrates are obtained using plating baths containing only NiSO4, ammonia, and an Al foil connected to the Cu substrate that serves as the electron source for Ni deposition (20 °C, 30 min).